Differential ceramic shell thickness evaluation for direct rapid investment casting - Omar, M. F. M. (2013)
Rapid prototyping (RP) process offers a promising economical way as a sacrificial pattern in investment casting (IC) at high speed and low cost for low volume part manufacturing. However direct sacrificial RP pattern have encountered shell cracking during burnout process due to polymer based materials. Shell mould thickness was need to be concerned to have strong enough to withstand RP part expansion for employing direct method. The aim of present research was to compare the efficacy of different shell thickness for aluminum casting part fabricated from acrylonitrile butadiene styrene (ABS) and acrylate based material made from FDM and MJM respectively. The hollow RP pattern has been used directly to produce ceramic moulds. The feasibility of ceramic mould has been assessed in term of burnout ability and crack defect. Dimensional accuracies and surface roughness of the castings part have been observed in this investigation. Result shows thicker mould with proposed stuco procedure resulted without any crack defect for botRP part and no residual ash remained when firing higher than 870°C of temperature.In addition, FDM produced better accuracy for overall mould thickness, but MJM have better surface roughness. Therefore both direct RP pattern were suitable to be used in IC process with proposed shell thickness.